Politeness in Computer-Mediated Pragmatics of Complaint Tweets by Clients of Ghanaian-based Telecom Networks - Sabayike, Latif Fuseini; ORFSON-OFFEIDr, Elizabeth Kwatekaa; Anderson, Jemima Asabea (International Journal of Language and Literary Studies, 2024)
This study investigates tweets of clients of three telecommunication networks in Ghana, to determine the various politeness strategies they employ while lodging complaints. 403 complaint tweets were purposively sampled and analyzed quantitatively and qualitatively using Brown and Levinson’s (1978, 1987) politeness framework and Anchimbe and Janney’s (2011) Postcolonial Pragmatics models. Results indicate that most complaints have some linguistic indicators that correspond to at least one of Brown and Levinson’s politeness strategies. Patterns emerging show that most complainants had suffered various network instabilities which had affected their daily routines; hence, causing them to make interrogative utterances with little or no mitigations. This probably accounted for the frequent use of more bald-on-record and negative politeness strategies than others. However, the competitive frequencies between positive and negative politeness strategies seem to align more with the cultural orientation of participants than a mere attempt to consider the face needs of network providers as argued by Brown and Levinson (1987).